Rodzina - wybór zawodu - szkoła - Pielka, Henryk (Wydawnictwo Naukowe UAM, 2000)
Family is a social group having a great influence on the choice of aims, values and creating the lite and professional ambitions of their children. In this environment a child’s attitude towards work is also adopted. The appropriate professional development gets its meaning in the new circumstances of a man’s life. Its course is determined by family factors supported by school conditons. A teacher is an organiser of school and family cooperation.
Family - profession choice of occupation -school